Making an Electric Vehicle Charging System as a learning tool for the community About Electric Vehicles - Adriyanto, Feri; Nizam, Muhammad; Anwar, Miftahul; Ramelan, Agus; Warindi, Warindi; Saputro, Joko Slamet; Inayati, Inayati (Jurnal Abdimas, 2023)
The purpose of this service program is to introduce coomunity in Magetan Regency to electric vehicle technology. The material presented is basic material covering the meaning, benefits, and components of electric vehicles using developing charging system prototipe. people who visit the Refugia Garden are asked to immediately try the electric vehicle and after completion are asked to carry out the charging process themselves. By observing and trying it directly, it is hoped that the community's main set of electric vehicles will be formed as a way to reduce carbon emissions.The purpose of this service program is to introduce coomunity in Magetan Regency to electric vehicle technology. The material presented is basic material covering the meaning, benefits, and components of electric vehicles using developing charging system prototipe. people who visit the Refugia Garden are asked to immediately try the electric vehicle and after completion are asked to carry out the charging process themselves. By observing and trying it directly, it is hoped that the community's main set of electric vehicles will be formed as a way to reduce carbon emissions.